2017
DOI: 10.1016/j.bjid.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired methicillin-resistant Staphylococcus aureus carrying SCC mec type IV and V isolated from healthy children attending public daycares in northeastern Brazil

Abstract: Nasal colonization with methicillin-resistant Staphylococcus aureus (MRSA) have increasingly been reported in healthy communities. This study aimed to assess the rate of S. aureus in general and MRSA in particular from nasal secretion of children in daycare centers in Vitória da Conquista, Brazil. The isolates were identified based on morphology, biochemical tests and by PCR. Detection of virulence genes, biofilm production, and susceptibility test by disk diffusion agar were performed. MRSA isolates were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…A study evaluated nasal carriage of MRSA 19 among 250 first and second year students from University of Londrina, in the South of the country, with a prevalence of 2.5%, a similar result to our study. Among 148 children in a daycare center in Northeastern Brazil, MRSA nasal carriage was 7.4% 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluated nasal carriage of MRSA 19 among 250 first and second year students from University of Londrina, in the South of the country, with a prevalence of 2.5%, a similar result to our study. Among 148 children in a daycare center in Northeastern Brazil, MRSA nasal carriage was 7.4% 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The isolates were inoculated aerobically at 37°C overnight on blood agar (Hi‐Media Laboratories, Mumbai, India). The strains of S. aureus were identified based on colony morphology, Gram's stain, and different biochemical tests, such as catalase and coagulase and growth at Mannitol Salt Agar (MSA) (Hi‐Media Laboratories, Mumbai, India), as a selective and differential medium …”
Section: Methodsmentioning
confidence: 99%
“…The percentage of children in day care facilities who carry the four major pathogens (Streptococcus pneumoniae, Hemophilus influenzae, Mycobacterium catarrhalis, and S. aureus) is higher than among children who do not attend day care facilities [6]. Adcock (1998) [5] and Carvalho (2017) [9] also reported the possibility of transmission of MRSA to other children in the same facility as well as to their parents. Many studies have reported the transfer of infectious disease among children or children and teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Children at a child care facility may play a role as a reservoir of resistant bacteria, and they can transfer resistant bacteria to family and community members, resulting in spread of resistance [4][5][6]. Some reports have described higher detection rates of methicillin-resistant Staphylococcus aureus (MRSA) and trimethoprim-resistant E. coli in children attending child care facilities than in those who do not attend a child care facility [7][8][9]. Adcock et al highlighted that resistant strains are spread to families and communities through person-toperson contact [5].…”
Section: Introductionmentioning
confidence: 99%